Determination of tea tree oil terpenes by headspace gas chromatography mass spectrometry. Issue 23 (25th May 2016) - Gallart-Mateu, D.; Rodriguez-Sojo, S.; de la Guardia, M.
Abstract : An alternative procedure was developed for determining quality control of terpenes in tea tree oil commercial samples. Abstract : An alternative procedure was developed for determining quality control of terpenes in tea tree oil commercial samples. The method is based on static headspace gas chromatography mass spectrometry measurements. Absolute limits of detection ranged from 1 ng for p -cymene to 71 ng for terpinen-4-ol. The accuracy of the developed methodology was evaluated by comparing the obtained eucalyptol and terpinen-4-ol concentrations with those provided for a certified sample and by comparing the developed procedure with literature tea tree oil analysis methodology. In the same way, spiked commercial samples provided recovery values ranging between 94% and 100% for all the target analytes with relative standard deviation values from 2% to 6%. The greenness of the developed methodology was evaluated by the Green Certificate ranking.